Parthian rock-reliefs from Amādiya in Iraqi-Kurdistan - Miglus, Peter A.; Brown, Michael; Aguilar Gutiérrez, Juan (Zeitschrift für Orient-Archäologie, 2018)
The ancient fortress of Amādiya is situated atop a mesa at the foot of the Zagros Mountains in Iraqi-Kurdistan. In front of the Mosul Gate there are two rock-reliefs depicting larger than life figures in traditional Parthian dress. This article presents detailed illustrations of these sculptures, using digital photogrammetry to enhance eroded features.